Monitoring of Pollution of Salmonella sp. in Raw Milk Using Virulence Gen Marker - Stefanie Yolanda Liwan; Tri Yahya Budiarso (Indonesian Association of Food Technologists, 2018)
Salmonella sp. is an enteropathogenic organism and it can spread through contaminated food which is rich in nutrition such as raw milk. The goal from this research is to find out the suitable pasteurization and time effect on the growth isolates Salmonella sp. that its invA presence is detected. Seventy-five (75) samples were taken in three locations of milk collection from groups of breeders. 10 ml of milk samples were grown in enrichment culture of modified Tryptic Soy Broth (mTSB) at 37oC for 12 hours. Cellular culture was then grown in differential selective medium of Salmonella Shigella Agar (SSA) and Chromocult Coliform Agar (CCA). From 75 milk samples produced 1392 colonies of typical Salmonella sp. pathogens. Then, isolates were selected using Triple Sugar Iron Agar (TSIA) and Urea Broth media, producing 3 suspected isolates of Salmonella sp which was known from colonies color. Results of confirmation using API 20E and 50 CHE produced two isolates of Salmonella spp. with %ID = 99.6% and one isolate of Salmonella typhi with %ID = 72.1%. All of the isolates were then detected for virulence factor using invA marker and all positive isolates have virulence factor. It indicates that raw milk contains polluted pathogenic bacteria.Keywords: raw milk, enteric pathogenic, virulence gen